Limestone-based closed reactor for passive treatment of highly acidic raw water - Mohd Kusin, Faradiella; Muhammad, Siti Nurjaliah; Md Zahar, Mohd Syakirin (Islamabad : K.A.J Printing Islamabad, 2014)
Limestone has been widely used in the treatment of acidic water due to its potential of neutralising acid and removing metals in water. In this study, the efficiency of a laboratory-scale limestone-based closed reactor was evaluated for treatment of highly acidic raw water. The treatment reactor was basically designed to enhance limestone dissolution and alkalinity generation under anoxic condition thus minimising the potential of armouring which may decrease the rate of acid neutralisation. Actual raw water from two different sources that is highly acidic with very low pH was used in the experiment, treated with 30mm diameter of 112kg of limestone. The conditions under which the pH increases, acidity decreases, alkalinity produced and metals were removed in the closed limestone reactor have been determined in comparison to open limestone channel performance. pH was significantly increased from 3.27-4.09 to 6.49-6.67 after flowing through the reactor in 10minutes of contact with the limestone. Acidity was reduced from 73-99 mg/L as CaCO3 to 17-19 mg/L as CaCO3 as pH were raised to reach near neutral levels. Iron and aluminium were also found removed in the closed limestone reactor.